FACTORS ASSOCIATED WITH ANTIRETROVIRAL THERAPY ADHERENCE AMONG PEOPLE LIVING WITH HIV/AIDS IN INDONESIA - Ikhwan Amirudin; Dhian Luluh Rohmawati; Denissa Faradita Aryani; Marnila Yasni; Azizati Salmas Marsiami (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Adherence to antiretroviral therapy (ART) is a crucial determinant of successful HIV/AIDS management, as it plays a key role in viral suppression, improvement of quality of life, and reduction of morbidity and mortality. Despite the expansion of ART programs in Indonesia, suboptimal adherence remains a significant challenge influenced by individual, social, and healthcare-related factors. This study aimed to analyze factors associated with antiretroviral therapy adherence among people living with HIV/AIDS (PLWHA) in Indonesia. A quantitative cross-sectional study was conducted in four provinces in Indonesia: Lampung, South Sumatra, West Java, and East Java. Participants were selected using a multistage sampling technique and met the predefined inclusion criteria. Data were collected using structured questionnaires covering socio-demographic characteristics, knowledge of ART, family support, healthcare provider support, access to health services, and ART adherence measured using the Morisky Medication Adherence Scale (MMAS-8). Data analysis included univariate and bivariate analyses using the chi-square test, with associations expressed as Prevalence Ratios (PR). The findings indicated that ART adherence was significantly associated with knowledge of ART (0,004), family support (0,011), healthcare provider support (0,003), and access to health services (0,031) (p < 0.05). Participants who had good knowledge, strong family support, and adequate support from healthcare providers were more likely to adhere to ART. Antiretroviral therapy adherence among PLWHA in Indonesia is influenced by knowledge, family support, healthcare provider involvement, and access to healthcare services. Strengthening patient education and optimizing the role of nurses in continuous counseling and support are essential strategies to improve ART adherence.